Motivations of retired professors to return to work activities at a public university - Ana Cláudia Souto Santos; Benedita Gonçalves de Assis Ribeiro; Júlia Trevisan Martins; Maria José Quina Galdino; Maria Lúcia do Carmo Cruz Robazzi; Renata Perfeito Ribeiro (Rev Rene)
Objective: to understand the motivations of professors of a public university to return to teaching after retirement. Methods: qualitative study carried out with 13 professors at a public university who returned to work activities after they retired. Data were collected through semi-structured interviews and analyzed using content analysis. Results: four categories emerged: the feeling of missing the contact with students, financial increase, peak of career experiencing idleness and disease. Conclusion: professors return to the same labor activity after retirement because of desire to remain experiencing feelings of well-being that work promotes, as well as to prevent illness resulting from idleness.